Narrative learning in coding activities: gender differences in middle school - Paolo Tosato; Monica Banzato (Pensa MultiMedia, 2017)
The recent introduction in Italy of Computational Thinking at the primary and secondary levels by the Educational Reform Act (October 2015) raises two critical issues: first, women are underrepresented in the computer field (OECD, 2015a; OECD, 2015b); second, girls lose their interest in computer sciences during adolescence (Gras-Velazquez et al., 2009). Therefore, the aim of this study is to investigate gender differences in self-efficacy and engagement through educational narrative methods for learning programming at middle school, a period considered critical in the research literature (Bandura, 1997; Pajares & Schunk, 2001a; Pajares & Schunk, 2001b). This is generally due to a decline in the self-efficacy beliefs of girls in science. Although this is an exploratory study, the implications that emerged show the potential of narrative educational activities to serve as a "cognitive bridge" to engage and improve the self-efficacy of the girls in computational thinking activities.